Understanding the Dynamism of Leadership Behavior, Style and Traits. - Sunil Kumar (Journal of Informatics Education and Research, 2024)
This study explores the dynamics of leadership by analyzing three key models- Stogdill (1974), Derue et al. (2011), and Gutterman (2023). These models provide complementary perspectives on leadership traits, behaviors, and emotional intelligence. Universal attributes like self-confidence and persistence intersect with adaptive behaviors and relational skills, emphasizing leadership's multidimensional nature. Emotional intelligence is highlighted as vital for addressing modern organizational challenges. Through a comparative analysis, this study synthesizes theoretical and practical insights, identifying overlaps and distinctions. The findings offer a comprehensive understanding of leadership and a foundation for future research in diverse organizational contexts.